2018
DOI: 10.1002/mnfr.201700804
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Impairs Oligopeptide/Amino Acid‐Induced Ghrelin Release and Smooth Muscle Contractions in the Human Proximal Stomach

Abstract: Region-specific targeting of AA taste receptors on both enteroendocrine and SM cells with specific AA-enriched diets might be a useful strategy to combat obesity as well as hypomotility disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 49 publications
(84 reference statements)
3
31
1
Order By: Relevance
“…The entire stomach and part of the small intestine (duodenum and jejunum) were collected from circulatory death or brain death organ donors (lean). Detailed protocols for tissue preparations from organ donors have been previously published (17). A large part of the stomach and a segment of the jejunum were obtained from obese nondiabetic patients who underwent sleeve gastrectomy or Roux‐en‐Y gastric bypass surgery, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The entire stomach and part of the small intestine (duodenum and jejunum) were collected from circulatory death or brain death organ donors (lean). Detailed protocols for tissue preparations from organ donors have been previously published (17). A large part of the stomach and a segment of the jejunum were obtained from obese nondiabetic patients who underwent sleeve gastrectomy or Roux‐en‐Y gastric bypass surgery, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The rise in plasma ghrelin levels before each meal is mediated by the sympathetic nervous system and involves β 1 ‐adrenergic receptors (AR) on the ghrelin cell in mice (1315). The magnitude of the postprandial decline is determined by the macronutrient composition of the meal and is partially regulated by taste receptors (16, 17).…”
mentioning
confidence: 99%
“…[63][64][65][66][67] In particular, the expression of αgustducin and α-transducin (both comprising G protein α-subunits detected in the gustatory system 68 ) in octanoyl ghrelin-producing cells indicates an important role in nutrient sensing processes. [63][64][65][66][67] In particular, the expression of αgustducin and α-transducin (both comprising G protein α-subunits detected in the gustatory system 68 ) in octanoyl ghrelin-producing cells indicates an important role in nutrient sensing processes.…”
Section: Stomachmentioning
confidence: 99%
“…In contrast, bitter substances activate 25 subtypes of the taste receptor type 2 (T2Rs) family. 16 Interestingly, the T1R3 subunit was expressed in mouse but not human fundic smooth muscle tissue. 6,10 A functional role for T1R1/T1R3 activation has also been demonstrated in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…A, Representative tracing illustrating the phasic contraction of the muscle strip from antrum in response to acetylcholine (ACh, 100 µmol/L) and inhibition of the amplitude and frequency of phasic contraction by MSG (100 mmol/L). Recent studies by Vancleef have identified the species-specific presence of mRNA transcripts for several types of L-AA receptors on human and mouse gastric tissues and the functional effect of their activation 16. B, Concentration-dependent inhibition of amplitude by MSG.…”
mentioning
confidence: 99%